Determinação do estado fundamental de compostos antiferromagnéticos da série Tb(1-x)Y(x)RhIn(5): aproximação teórico experimental - Amaral, Robert Prudêncio (2016)
We present the results of electrical resistivity, magnetic susceptibility, specific heat and x-ray absorption spectroscopy measurements in Tb1−xYxRhIn5 (x = 0.00, 0.15, 0.4.0, 0.50 e 0.70) single crystals. Tb1−xYxRhIn5 is an antiferromagnetic AFM compound with ordering temperature TN ≈ 46 K, the higher TN within the RRhIn5 serie (R : rare earth). We evaluate the physical properties evolution and the supression of the AFM state considering doping and Crystalline Electric Field (CEF) effects on magnetic exchange interaction between Tb3+ magnetic ions. CEF acts like a perturbation potential, breaking the (2J + 1) multiplet s degeneracy. Also, we studied linear-polarization-dependent soft x-ray absorption at Tb M4 and M5 edges to validate X-ray Absorption Spectroscopy as a complementary technique in determining the rare earth CEF ground state. Samples were grown by the indium excess flux and the experimental data (magnetic susceptibility and specific heat) were adjusted with a mean field model that takes account magnetic exchange interaction between first neighbors and CEF effects. XAS experiments were carried on Total Electron Yield mode at Laborat´onio Nacional de Luz S´ıncrotron, Campinas. We measured X-ray absorption at Tb M4,5 edges with incident polarized X-ray beam parallel and perpendicular to c-axis (E || c e E ⊥ c). The mean field model simulates the mean behavior of the whole system and, due to many independent parameters, gives a non unique CEF scheme. XAS is site- and elemental- specific technique and gained the scientific community s attention as complementary technique in determining CEF ground state in rare earth based compounds. In this work we wil discuss the non conclusive results of XAS technique in TbRhIn5 compounds.